Morning Bright Light Treatment for Sleep-Wake Disturbances in Primary Biliary Cholangitis: A Pilot Study - Turco, Matteo; Cazzagon, Nora; Franceschet, Irene; Formentin, Chiara; Frighetto, Giovanni; Giordani, Francesca; Cellini, Nicola; Mazzotta, Gabriella; Costa, Rodolfo; Middleton, Benita; Skene, Debra J.; Floreani, Annarosa; et al. (Frontiers in Physiology, 2018)
Patients with Primary Biliary Cholangitis (PBC) exhibit delayed sleep-wake habits, disturbed night sleep and daytime sleepiness/fatigue. Such combination of symptoms is reminiscent of delayed sleep-wake phase disorder (DSPD), which benefits from morning light treatment. The aim of the present pilot study was to test the effect of morning light treatment in a group of 13 well-characterized patients with PBC [all females; (mean ± SD) 53±10 yrs]. Six healthy individuals (4 females, 57±14 yrs) and 7 patients with cirrhosis (1 female, 57±12 yrs) served as controls and disease controls, respectively. At baseline, all participants underwent an assessment of quality of life, diurnal preference, sleep quality/timing (subjective plus actigraphy), daytime sleepiness, and urinary 6-sulphatoxymelatonin (aMT6s) rhythmicity. Then they underwent a 15-day course of morning bright light treatment, immediately after getting up (light box, 10000 lux, 45 mins) whilst monitoring sleep-wake patterns and aMT6s rhythmicity. At baseline, both patients with PBC and patients with cirrhosis had significantly worse subjective sleep quality compared to controls. In patients with PBC, light treatment resulted in an improvement in subjective sleep quality and a reduction in daytime sleepiness. In addition, both their sleep onset and get-up time were significantly advanced. Finally, the robustness of aMT6s rhythmicity (i.e. strength of the cosinor fit) increased after light administration but post hoc comparisons were not significant in any of the groups. In conclusion, a brief course of morning bright light treatment had positive effects on subjective sleep quality, daytime sleepiness and sleep timing in patients with PBC. This unobtrusive, side-effect free, non-pharmacological treatment is worthy of further study.